2013
DOI: 10.1111/cid.12181
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of Circumferential Defects with Osseoconductive Xenografts of Different Porosities: A Histological, Histometric, Resonance Frequency Analysis, and Micro‐CT Study in Dogs

Abstract: The high-porosity block (DBBM block) failed to provide greater bone repair within the defect. Biomaterials with lower porosity (DBBM sponge and granules) showed similar or higher bone formation when compared with autogenous bone.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
14
0
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(18 citation statements)
references
References 55 publications
1
14
0
3
Order By: Relevance
“…Many case series reported good clinical outcomes from DBBM blocks used in onlay [3031] and inlay procedures [3233]. Nevertheless, some authors have reported that DBBM blocks pose difficulties for the invasion of newly formed bone, which was primarily found in proximity to native medullary bone or periosteum, both in onlay [34] and inlay [35] grafts. Such findings were confirmed by our morphometric analysis of CA, which was mainly composed of residual DBBM both at 1 month and 3 months of observation.…”
Section: Discussionmentioning
confidence: 99%
“…Many case series reported good clinical outcomes from DBBM blocks used in onlay [3031] and inlay procedures [3233]. Nevertheless, some authors have reported that DBBM blocks pose difficulties for the invasion of newly formed bone, which was primarily found in proximity to native medullary bone or periosteum, both in onlay [34] and inlay [35] grafts. Such findings were confirmed by our morphometric analysis of CA, which was mainly composed of residual DBBM both at 1 month and 3 months of observation.…”
Section: Discussionmentioning
confidence: 99%
“…-модификация исходного ксеноматрикса (развитие технологии очистки, изменение структуры и химического состава матрикса кости) [58,59,60,61,62,63,64,65,66,67,68];…”
Section: результатыunclassified
“…Импрегнация биологически активными веществами Факторы роста [41,42,43,44,45] Антибиотики [46,47] Антибиотики + Факторы роста [48] Бисфосфонаты [49] Плазма, обогащенная тромбоцитами [50] Тканевая инженерия Обогащение ксеноматрикса стволовыми клетками [51,52,53,54,55,56,57] Химическая модификация ксеноматрикса Включение ионов фтора [58] Включение ионов хлора [59] Включение ионов магния [60] Химическая сшивка биополимеров [61] Физическая модификация ксеноматрикса Изменение пористости [62,63] Изменение кристалличности [64] Совершенствование технологии очистки Депротеинизация [65] Извлечение липидов [66] Новые источники ксеноматериала Роговая кость [67] Кролики, лошадь [68] Выполненный анализ показал, что костнопластические материалы ксеногенного происхождения в настоящее время в практической травматологии и ортопедии используются при лечении ограниченного спектра патологий, в отличие от челюстно-лицевой хирургии и стоматологии, где накоплен большой опыт применения этих материалов для замещения костных дефектов, а также сформированы собственные протоколы имплантации. Тем не менее, можно ожидать рост востребованности ксеноматериалов в травматологии и ортопедии, связанный с увеличением клинического спроса на костнопластические материалы, который, в частности, вызван увеличением числа ревизионных операций эндопротезирования, требующих восполнения недостатка костной ткани.…”
Section: направление тип модификации источникunclassified
“…In the control sites, no bone grafts or barrier membranes were used. He listed that the filling of the peri-implant bone defects with autogenous bone grafts showed a better outcome compared to unfilled defects (5) .…”
Section: Introductionmentioning
confidence: 99%